PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN CAREFAST GRAND JATI JUNCTION - Tanjung, Oppie Meisya; Gulo, Septi Damai Putri; Lawolo, Sefilina Putri (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study aims to analyze the influence of work motivation and work discipline on employee performance. This study adopts a quantitative associative methodology, the population in this study are all employees at Carefast Grand Jati Junction. To determine the sample size, using a saturated sample method where all members of the population are used to fill out a questionnaire with a Likert scale. The collected data were then analyzed using the SPSS approach. The findings of the study revealed that partially work motivation has a significant effect on the performance of Carefast Grand Jati Junction employees, work discipline does not affect the performance of Carefast Grand Jati Junction employees, simultaneously work motivation and work discipline have a significant effect on the performance of Carefast Grand Jati Junction employees